2020 International Conference on Software, Telecommunications and Computer Networks (SoftCOM) 2020
DOI: 10.23919/softcom50211.2020.9238249
|View full text |Cite
|
Sign up to set email alerts
|

MAC-aware Routing Protocols for Vehicular Ad Hoc Networks: A Survey

Abstract: The constantly growing number of vehicles on our roads has become an increasing major cause of serious injury and death. Efficient data dissemination in Vehicular Ad hoc Networks (VANETs) inevitably requires an efficient and robust routing protocol. In this context, several categories of routing protocols have been proposed in the literature to meet VANETs application requirements in terms of delay, packet loss and throughput. In this paper, we focus on cross layer routing protocols. We present a survey of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…VNs [3]- [8] have been extensively studied in different contexts, and recently published surveys cover many aspects of the VNs. Several surveys focus on the Quality-of-Service (QoS) of VNs involving the Medium Access Control (MAC) protocols [9]- [13], routing or message dissemination solutions [14]- [22], energy harvesting techniques [23], [24], and mobility management [25]. Furthermore, considering the vulnerability of VNs to various attacks, a great deal of studies investigate the security [26]- [28], privacy [29]- [32], trust [33], and comprehensive aspects (the former three metrics) [34], [35] of VNs.…”
Section: Sdn-based Vns Uav-assisted Vnsmentioning
confidence: 99%
“…VNs [3]- [8] have been extensively studied in different contexts, and recently published surveys cover many aspects of the VNs. Several surveys focus on the Quality-of-Service (QoS) of VNs involving the Medium Access Control (MAC) protocols [9]- [13], routing or message dissemination solutions [14]- [22], energy harvesting techniques [23], [24], and mobility management [25]. Furthermore, considering the vulnerability of VNs to various attacks, a great deal of studies investigate the security [26]- [28], privacy [29]- [32], trust [33], and comprehensive aspects (the former three metrics) [34], [35] of VNs.…”
Section: Sdn-based Vns Uav-assisted Vnsmentioning
confidence: 99%
“…The new directions in research related to seamless connectivity, edge, fog, SDN, and security are also focused. An in-depth survey and comparison of vehicular MAC routing protocols was conducted in [37]. It addressed routing protocols with a cross-layer approach with MAC for VANETs.…”
Section: Cellular-based Networkmentioning
confidence: 99%
“…These proposals make use of different parameters from the MAC layer, like transmission time slot allocation, channel state, and collision probability, to improve data dissemination in VANETs. A detailed review of these cross-layer routing approaches for VANET is given in [25]. In this section, we focus on solutions dedicated to multi-hop emergency messages broadcast.…”
Section: Related Workmentioning
confidence: 99%
“…Cross-Layer design is an emerging proposal to support flexible layer approaches in VANETs [25]. As described above, the recent ongoing research has shown increased interest in protocols that rely on interactions between different layers.…”
Section: Cross-layer Solution For Emergency Messages Multi-hop Disseminationmentioning
confidence: 99%